Movement Pattern Recognition Abilities Among Expert and Non-Expert Malaysian Rhythmic Gymnasts - Teh, Lah Hoong (2003)
The superior performance of experts over novices has been attributed to specific hardware and/or software differences in the past. Recent sport research has also indicated the prominence of cognition differences in the performance of athletes. Using the expert-nonexpert paradigm, this study examined the movement pattern recognition abilities of eighteen trained Malaysian rhythmic gymnasts who were ranked accordingly to their performance in the recent National Junior Championship, and nine girls who make up the control group. Research participants performed a resequencing task within a specific time frame on a set of five rhythmic gymnastic movement sequences involving pirouttes and rotations. The data was collected from the trained gymnasts of the seven rhythmic gymnastics training centres where they were attached . The main statistical procedure used was the one-way ANOVA with the Bonferroni procedure used for post-hoc analyses. ANOVA was used to verify the hypothesis. Primary findings showed that there are significant differences in the movement pattern recognition abilities among the expert and non-expert Malaysian rhythmic gymnasts. In sum, the findings indicated significant differences between the expert gymnasts and nonexpert gymnasts in the hoop, clubs and ribbon movement sequences used. However, no significant differences were found between the nonexpert gymnasts and the control group in the movement pattern recognition abilities assigned in this experiment. The results demonstrated evidence of a significant difference in terms of movement pattern recognition abilities among the expert and non-expert Malaysian rhythmic gymnasts from the seven training centres.